Phase Transition of the Higher Dimensional Charged Gauss-Bonnet Black Hole in de Sitter Spacetime - Meng-Sen Ma; Li-Chun Zhang; Hui-Hua Zhao; Ren Zhao (Advances in High Energy Physics)
We study the phase transition of charged Gauss-Bonnet-de Sitter (GB-dS) black hole. For black holes in de Sitter spacetime, there is not only black hole horizon, but also cosmological horizon. The thermodynamic quantities on both horizons satisfy the first law of the black hole thermodynamics, respectively; moreover, there are additional connections between them. Using the effective temperature approach, we obtained the effective thermodynamic quantities of charged GB-dS black hole. According to Ehrenfest classification, we calculate some response functions and plot their figures, from which one can see that the spacetime undergoes a second-order phase transition at the critical point. It is shown that the critical values of effective temperature and pressure decrease with the increase of the value of GB parameter α.